How political are national identities? A comparison of the United States, the United Kingdom, and Germany in the 2010s. (September 2018) - Mader, Matthias; Scotto, Thomas J.; Reifler, Jason; Gries, Peter H.; Isernia, Pierangelo; Schoen, Harald
Research demonstrates the multi-dimensional nature of American identity arguing that the normative content of American identity relates to political ideologies in the United States, but the sense of belonging to the nation does not. This paper replicates that analysis and extends it to the German and British cases. Exploratory structural equation modeling attests to cross-cultural validity of measures of the sense of belonging and norms of uncritical loyalty and engagement for positive change. In the 2010s, we find partisanship and ideology in all three nations explains levels of belonging and the two content dimensions. Interestingly, those identifying with major parties of the left and right in all three countries have a higher sense of belonging and uncritical loyalty than their moderate counterparts. The relationship between partisanship, ideology, and national identity seems to wax and wane over time, presumably because elite political discourse linking party or ideology to identity varies from one political moment to the next.